Professor Stanislaw Mondelski – the prominent ophthalmologist in Poznan. In the twentieth anniversary of the death - Kazało, Tomasz; Grzybowski, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Stanisław Mondelski was born the 21.01.1914 in Tarnow. He graduated the University of Medical Siences in 1948. He became the professor of the Ophtalmology Departament of the University of Medical Siences in Poznan in 1983. He was the author of above 100 scientific works. The subject matter of works concerned of the diagnosis and the treatment of the illnesses of retina, the oculistic oncology, improving the diagnostic methods and the operating techniques, the relationship between the eyes diseases and the general condition of the human organism, the treatment of glaucoma. Beyond the scientific and didactic activity, he dedicated many attentions to improving and constructing the investigative and healing apparatus. Professor Stanisław Mondelski died in 1992 in Poznan.